3y-3=-13-7y

Simple and best practice solution for 3y-3=-13-7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-3=-13-7y equation:


Simplifying
3y + -3 = -13 + -7y

Reorder the terms:
-3 + 3y = -13 + -7y

Solving
-3 + 3y = -13 + -7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7y' to each side of the equation.
-3 + 3y + 7y = -13 + -7y + 7y

Combine like terms: 3y + 7y = 10y
-3 + 10y = -13 + -7y + 7y

Combine like terms: -7y + 7y = 0
-3 + 10y = -13 + 0
-3 + 10y = -13

Add '3' to each side of the equation.
-3 + 3 + 10y = -13 + 3

Combine like terms: -3 + 3 = 0
0 + 10y = -13 + 3
10y = -13 + 3

Combine like terms: -13 + 3 = -10
10y = -10

Divide each side by '10'.
y = -1

Simplifying
y = -1

See similar equations:

| 12b-4=2b-24 | | 4y-2+y+33=7y+40-5y | | 8x-7-3x=8 | | 2(x+4)=x-2 | | 0.9=5d+0.4 | | -5d+5=10 | | 4(3+5x)-1=51 | | 3n-4=-13 | | 4x-6x=6 | | 3(2x+1)-2(2x+1)=10 | | -6x-9x=-60 | | (1.2)(-5)= | | (-9x^2+3x-7)+(-4x^2-x)= | | 3x+4=-59 | | x^2+14x+42=0 | | 3x^2+1=2x | | 2x^2+16x=66 | | 8x=-25 | | 2z-3y-8z+1y= | | 3(x-2)-9=0 | | 2z-3y-8z-1y= | | 2-x=5 | | (5m+2n-4)-(2m-3n-7)= | | 3a+2+1= | | 2(x+7)=(2x+14) | | (4x-11)=(x+6) | | 3x-5x+17=12-(6x+3) | | x(x+1)-3(x+1)= | | 8x^2-4x+2=0 | | 9+2m=-3-4m | | x(x+3)-5(x+3)= | | 45=0.5(6+3) |

Equations solver categories